2017
DOI: 10.1039/c7py00158d
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic polypyrroles synthesized by aqueous chemical oxidative polymerization and their use as light-responsive liquid marble stabilizers

Abstract: Hydrophobic polypyrroles doped with perfluoroalkyl dopants can function as a liquid marble stabilizer with photothermal properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 40 publications
3
67
0
Order By: Relevance
“…The electrical conductivities increased from 5.1 to 13.9 S cm −1 with an increase of BEHSS concentration in Py/BEHSS molar ratio range between 3/0 and 3/0.5. This result is consistent with the earlier finding that the conductivity of PPy increased by introduction of (perfluoro)alkyl dopants carrying sulfonate groups 31 . Above the Py/BEHSS molar ratio of 3/1, the conductivity decreased to 11.1 S cm −1 .…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The electrical conductivities increased from 5.1 to 13.9 S cm −1 with an increase of BEHSS concentration in Py/BEHSS molar ratio range between 3/0 and 3/0.5. This result is consistent with the earlier finding that the conductivity of PPy increased by introduction of (perfluoro)alkyl dopants carrying sulfonate groups 31 . Above the Py/BEHSS molar ratio of 3/1, the conductivity decreased to 11.1 S cm −1 .…”
Section: Resultssupporting
confidence: 93%
“…These results suggested that a surface tension gradient of 0.15 mN/m (72.27–72.12 mN/m 70 ) was generated around the LM. This surface tension gradient was smaller than those measured for the NIR laser‐induced motions of LMs stabilized by fluorinated dopant‐doped PPy, PANI and PEDOT grains (1.6–3.4 mN/m), 31–33,35 but definitely contributed to the generation of the Marangoni flow, which can work as the driving force of the LM motion. The motions of LM were videotaped and numerically analyzed (Figure 10a).…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Liquid marbles placed on a liquid support may be effectively propelled by soluto-capillary 38−40 and thermo-capillary Marangoni flows. 41,42 In our present work, we demonstrate that liquid marbles containing sulfuric acid may be effectively displaced by thermo-capillary Marangoni flow. 43−49 Self-propulsion took place under breaking of cylindrical symmetry of the water surface tension distribution in the vicinity of the marble contact area.…”
Section: Introductionsupporting
confidence: 51%